Analisis hukum Taghyir Khalqillah dalam fatwa perubatan badan fatwa terpilih / Mohammad Naqib Hamdan - Mohammad Naqib , Hamdan (2018)
The development of the medical world today provides a wide range of procedures for patients and partly affects the physical of patients, particularly in reconstructive, plastic and cosmetic surgery. Basically, taghy?r khalqill?h is prohibited by Allah SWT as found in surah al-Nis?ï¿½, verse 119 and the prohibitions from the had?th of al-wasl, al-washm, al-nams dan al-tafalluj. Hence, this study will explain the concept of taghyr khalqillh according to Islamic views through analysis of the perspectives of mufassir?n, muhaddith?n and fuqah?ï¿½. Researcher will also analyze the current resolutions and fatwa texts associated with the taghy?r khalqill?h. This study uses qualitative research method by combining document study and case study. A total of 12 mufassir?n, 18 muhaddith?n and 18 fuqah?ï¿½ were selected for document studies and 139 resolutions and fatwas from 10 major fatwa bodies for case studies. By using thematic analysis, this study found that the scholars use the concept of maqasid in determination of Islamic ruling by classifying taghy?r to three levels, ie. taghy?r dar?r?, h?j? and tahs?n?. In this study, only the criteria of taghy?r tahs?n? being developed because taghy?r dar?r? and taghy?r h?j? are allowed by the scholars in their necessary space. While taghy?r tahsini has no specific guidance. An analysis of 139 texts and medical fatwa related to taghy?r khalqill?h found that 67% of them use maqasid consideration in determining the Islamic ruling. Hence, the suggested concept and criteria of khalqillah can be a guidance to state fatwa bodies in deciding fatwa on medical issues. Doctors and patients may also refer to the guidance in determine medical treatment procedures allowed by shariah.